Effect of Intravenous Mannitol on Intraocular Pressure Changes in Vitrectomized Silicon-Oil-Filled and Non Vitrectomized Eyes: A Prospective Comparative Study - Naseer Ahmad, Faisal Nawaz, Asif Ali, Abdul Munim, Abdul Rafe, Haroon Saleem, Mir Ali Shah (Pakistan Journal of Medical & Health Sciences, 2023)
Purpose: Our studies turned into designed to assess the consequences of intravenous mannitol on intraocular pressure (IOP) in vitrectomized silicon-oil-stuffed eyes and to assessment those consequences with the ones received in non-vitrectomized eyes. Study Design: Prospective comparative case study Place and Duration: Ophthalmology department, Peshawar Medical College and affiliated hospitals, Peshawar for the duration from 1st Jan, 2022 to 30th June, 2022. Materials and Methods: All eyes with intraocular pressure lower than 38 mm Hg were considered. Group 1 had their vitreous removed and filled with silicon oil to reduce IOP, whereas Group 2 had their vitreous removed and their eyes were left open (Group 2). Mannitol (20 percent solution, 1 g/kg) was infused over the course of 30 minutes, and intraocular pressure was measured every 30 minutes during the first 2 hours, then again at the 3rd, 4th, and 6th hours post-administration. Results: In all, 36 eyes from each group were used. Group 1 had a decrease in mean (SD) IOP from 46.4 4.0 to 41.5 6.8 at 30 minutes, 38.5 ± 7.2 at 60 proceedings, 35.1 ± 7.5 at 90 records, 33.4 ± 9.3 at 2 hours, 31.8 ±9.5 at 3 hours, 30.8 ±10 at 4 hours, and 30.7 ± 9.9 at 6 hours, whereas group 2 saw a decrease in mean (SD) IOP from 46.9 5.4 IOP dropped significantly from baseline in all groups at all-time points up to 4 hours (P0.001). While both groups saw a reduction in intraocular pressure (IOP) after 4 and 6 hours of mannitol administration, there was no significant difference between the groups. Conclusion: Mannitol has been shown to dramatically lower IOP in both vitrectomized eyes with silicon fillings and non-vitrectomized eyes. Keywords: Mannitol, Intraocular pressure, Silicon-oil-filled eye, Vitrectomy